Unemployment dynamics in the OECD - National Bureau of Economic Research, Cambridge; Elsby, Michael; Hobijn, Bart; Sahin, Aysegul (Cambridge, MA, 2008)
"We provide a set of comparable estimates for the rates of inflow to and outflow from unemployment for fourteen OECD economies using publicly available data. We then devise a method to decompose changes in unemployment into contributions accounted for by changes in inflow and outflow rates for cases where unemployment deviates from its flow steady state, as it does in many countries. Our decomposition reveals that fluctuations in both inflow and outflow rates contribute substantially to unemployment variation within countries. For Anglo-Saxon economies we find approximately a 20:80 inflow/outflow split to unemployment variation, while for Continental European countries, we observe much closer to a 50:50 split. Using the estimated flow rates we compute gross worker flows into and out of unemployment. In all economies we observe that increases in inflows lead increases in unemployment, whereas outflows lag a ramp up in unemployment."